1987
DOI: 10.1007/bf00915210
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in professional help seeking among adult black Americans

Abstract: This paper provides baseline data on sex differences in the use of professional help for serious personal problems in a nationallyThe purpose of this paper was to provide baseline data on sex differences in help-seeking behavior among black adults. Seeking professional help can be conceptualized as a series of decisions: the recognition of a problem, the decision to seek some form of professional assistance, and the choice of a particular help source. This study was concerned with the last two decisions. That … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 22 publications
9
67
1
Order By: Relevance
“…These findings are consistent with previous research assessing athletes' attitudes toward and expectations of sport psychology consulting (e.g., Martin et al, 1997), in which male athletes seem to identify with their own ethnicity, culture, or race more than do female athletes. Findings related to healthcare and prevention have been remarkably consistent and have shown that, as a group, men of different ages (e.g., Husaini, Moore, & Cain, 1994), nationalities (e.g., D 'Arcy & Schmitz, 1979), and ethnic and racial backgrounds (Neighbors & Howard, 1987) seek professional help less frequently than do women (see Addis & Mahalik, 2003). Moller-Leimkuhler (2000) suggests that traditional social or cultural norms associated with masculinity, such as the inhibition of emotional expression, may hinder reporting and helpseeking in males.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous research assessing athletes' attitudes toward and expectations of sport psychology consulting (e.g., Martin et al, 1997), in which male athletes seem to identify with their own ethnicity, culture, or race more than do female athletes. Findings related to healthcare and prevention have been remarkably consistent and have shown that, as a group, men of different ages (e.g., Husaini, Moore, & Cain, 1994), nationalities (e.g., D 'Arcy & Schmitz, 1979), and ethnic and racial backgrounds (Neighbors & Howard, 1987) seek professional help less frequently than do women (see Addis & Mahalik, 2003). Moller-Leimkuhler (2000) suggests that traditional social or cultural norms associated with masculinity, such as the inhibition of emotional expression, may hinder reporting and helpseeking in males.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of their unwillingness to rely on others, men of different ages (Husaini, Moore, & Cain, 1994), nationalities (D'Arcy & Schmitz, 1979), and racial and ethnic backgrounds (Neighbors & Howard, 1987) are less likely than women to seek and accept professional help. Indeed, men are less likely to seek help for causes as diverse as depression, substance abuse, marital difficulties, and chronic stress (Husaini et al, 1994;Lewis & O'Brien, 1987;McKay, Rutherford, Cacciola, & Kabasakalian-McKay, 1996;Padesky & Hammen, 1981;Thom, 1986;Weissman & Klerman, 1977).…”
Section: Self-reliance and Adjustment To Prostate Cancermentioning
confidence: 99%
“…Neighbors and Howard (1987) found that African American men who sought counseling services varied in severity of mental health symptomology. This may be a result of multiple factors including presenting problem, socioeconomic status, access to healthcare, et cetera.…”
Section: Resultsmentioning
confidence: 99%